Role of G-protein coupled receptors in cardiovascular diseases - Li, Yuanqiang; Li, Boyu; Chen, Wei-Dong; Wang, Yan-Dong (Frontiers in Cardiovascular Medicine, 2023)
Cardiovascular diseases (CVDs) are the leading cause of death globally, with CVDs accounting for nearly 30% of deaths worldwide each year. G-protein-coupled receptors (GPCRs) are the most prominent family of receptors on the cell surface, and play an essential regulating cellular physiology and pathology. Some GPCR antagonists, such as β-blockers, are standard therapy for the treatment of CVDs. In addition, nearly one-third of the drugs used to treat CVDs target GPCRs. All the evidence demonstrates the crucial role of GPCRs in CVDs. Over the past decades, studies on the structure and function of GPCRs have identified many targets for the treatment of CVDs. In this review, we summarize and discuss the role of GPCRs in the function of the cardiovascular system from both vascular and heart perspectives, then analyze the complex ways in which multiple GPCRs exert regulatory functions in vascular and heart diseases. We hope to provide new ideas for the treatment of CVDs and the development of novel drugs.